Does corporate social responsibility affect the participation of minority shareholders in corporate governance? - Kong, Dongmin (Journal of Business Economics and Management, 2013)
Using a unique minority shareholders voting dataset, we aim to shed light on several important issues on corporate governance and investor protection. Specifically, we first examine the effects of social responsibility (CSR) on minority shareholder participation (MSP). Then, we investigate whether the mounting attention to CSR due to certain events has marginal effects on MSP, and whether CSR and MSP affect firms’ market performances. Collectively, we find that: 1) firms’ CSR levels significantly affect MSP and can substitute the governance role of minority shareholders to some extent; 2) exogenous shocks related to CSR can significantly affect MSP; and 3) firms with higher CSR level and lower MSP enjoy higher market value improvements. In addition, we find limited evidence that institutional investors may face conflict-of-interest pressures and vote against individual investors. Our results are robust to alternative specifications and offer significant policy implications.